ASSESSMENT OF CRACKING RESISTANCE OF CELLULAR CONCRETE PRODUCTS UNDER MOISTURE AND CARBONISATION DEFORMATIONS WITH STRESS RELAXATION - Sh. I. Apkarov; D. K.-S. Bataev; M. A. Gaziev; Kh. N. Mazhiev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. On the basis of the experimental, theoretical and field studies, an engineering calculation method was developed for assessing the cracking resistance of external enclosing constructions made of cellular concrete, with the maximum gradient development of moisture and carbonisation forced deformations along their thickness, taking into account the relaxation of the shrinkage stresses. In this regard, the aim of the work is to provide technological measures at the manufacturing stage in order to increase the operational cracking resistance of the construction's outer surface layers by reducing the moisture and carbonation shrinkage of cellular concrete by introducing a large or fine porous aggregate in calculated amounts.Methods. A number of analytical equations were applied to establish the dependence of the shrinkage of heavy concrete of conventional hardness on the amount of aggregate introduced and its elasticity modulus, water-cement ratio and cement consumption, as well as the concrete's moisture content.Results. Knowing the volumes of the structural aggregate and the cellular concrete mass, as well as their modulus of elasticity, the shrinkage reduction factor of the cellular concrete was calculated with the addition of a lightweight porous aggregate. Subsequently, the shrinkage deformations of concrete in the surface layer of the outer enclosing construction, maximising crack resistance due to moisture exchange and carbonation influences under operating conditions, were defined, taking into account the relaxation of tensile stresses due to creep of concrete.Conclusion. Theoretical calculations, based on the recommended method of assessing the cracking resistance of cellular concrete enclosing constructions under moisture exchange and carbonisation processes, taking into account the relaxation of shrinkage stresses, showed that in order to exclude the appearance of cracks in wall panels 280 mm thick made of 700 kg/m3 gas ash concrete with elasticity modulus of 2500 MPa, it is necessary to have 70-80% of keramzite or granulated slag, and 50-60% of stone crumb (granite or marble crushed stone) of the volume of cellular concrete in the surface layer of 30-50 mm.